Impacts of invasive plant species on arbuscular mycorrhizal fungi: consequences for ecosystem functions and plant communities - Singh, Meenakshi; Chauhan, Ambika; Singh, Pradeep Kumar (International journal of environmental studies, 2025)
Arbuscular mycorrhizal fungi (AMF) are critical for ecosystem functioning and plant growth, enhancing nutrient uptake and soil stability. Invasive plant species (IPS) can disrupt AMF communities, reducing diversity and altering symbiotic interactions. This review examines IPS impacts on AMF colonisation, diversity, and plant communities across ecosystems. IPS-driven changes in AMF affect plant competition, nutrient cycling, and carbon sequestration, destabilising ecosystems. Understanding these interactions is essential for ecosystem management. Future research should explore long-term IPS_AMF dynamics and develop targeted strategies to mitigate IPS effects.